1/42.0 KCS 모형선의 조종성능에 관한 연구 - 윤근항(Kunhang Yun); 김동진(Dong Jin Kim); 연성모(SeongMo Yeon); 김유철(Yoo-Chul Kim); 김연규(Yeon Gyu Kim); 양경규(Kyung-Kyu Yang) (大韓造船學會 論文集, 2022)
The emergence of new concept ships, such as autonomous ships, has drawn much attention on the manoeuvrability of ships because of the safe navigation and operation of ships. Although the manoeuvrability of KRISO Container Ship(KCS) has been frequently reported, there have been few documents of representative manoeuvre cases conducted in various methods by one institute. This paper presents the manoeuvrability of the ship in 1/42.0 model scale by 3 methods: free running model tests, horizontal planar motion mechanism tests, and computational fluid dynamics analysis. KRISO reports KCS manoeuvre data: 35° turning circle tests and 20/20(10/10) zigzag manoeuvring tests. In addition, a simple formula for integrating and comparing manoeuvre indices, Manoeuvrability Comparing Simple Index(MCSI), is proposed.